Resilience-based design optimization of engineering systems under degradation and different maintenance strategy - Wang, Zhonglai; Wen, Yang; Wang, Zhihua; Zhi, Pengpeng (Structural and multidisciplinary optimization, 2023)
Resilience-based design optimization is an effective way to design the high resilience into engineering systems during the design stage. Addressing the continuous degradation, discrete shocks, and different maintenance strategy, the resilience-based design optimization model and algorithms are proposed to ensure the operational safety of engineering systems in this paper. The unified framework of resilience under the continuous degradation, discrete shock, and different maintenance strategy is first proposed. The surrogate model to estimate the time-variant reliability under the continuous stochastic process and discrete Poisson process is then constructed. The mapping function between the performance improvement ratio and the maintenance strategy is defined to build the lifecycle cost models. The combination of Kriging surrogate model and particle swarm optimization is finally provided to conduct resilience-based design optimization. An engineering case of a harmonic reducer used for the lower extremity exoskeleton is employed to illustrate and testify the effectiveness of the proposed methods.